BIODEGRADATION OF POLYURETAN RESULTS OF SYNTHESIS OF SOYBEAN OIL, GLYCOLOLY POLYOKYLETHLES, AND METHYLES-4,4'-DIFENILDIISOSIANAT - Eli Rohaeti; Senam Senam (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2010)
The objective of research were to synthesize polyurethane from soybean oil, P EG400 and MDI, to determine the cross linking, and to learn the influence of incubation times toward degradability of polyurethane. Polyurethane was synthesized from soybean oil and oxydated soybean oil at room temperature followed by curing for 10 hours at 70 DC,and than at 100